Evaluasi Program Pelatihan dalam Pengingkatan Kompetensi Guru di PAUD : Systematic Literature Review - Izza Mutia Raihan; Nurhattati Nurhattati; Kamaludin Kamaludin (Departement of Mathematics Education, 2025)
This research aims to systematically analyze early childhood education teacher training programs through a systematic review approach. The study focused on evaluating the effectiveness of training programs in improving early childhood teachers' competencies, identifying factors influencing program success, and formulating development recommendations. The research methodology employed a systematic review analyzing 15 research articles published between 2010-2024, selected from various academic databases using the PRISMA protocol. Results indicate that effective training programs are characterized by comprehensive, sustainable, and contextual approaches. Teacher competency improvements were significant in pedagogical, professional, social, and personal aspects. Success factors include teachers' internal motivation, facilitation quality, and institutional support. Major challenges encompass digital disparities, resource limitations, and socio-economic complexities. The research recommends developing blended learning-based training models and strengthening multi-stakeholder partnerships to optimize early childhood teacher training programs.